Local delivery of virgin coconut oil as an adjunct to non-surgical periodontal treatment: a randomised clinical trial - Azmi, Nur Shahira Azmi (2024)
Introduction: Eliminating dental bio film within deep periodontal pockets measuring 5 mm and more poses significant challenges. Therefore, supplementing subgingival instrumentations with localised antimicrobial delivery could aid in the eradication of microbes at the pocket base. Objectives: To evaluate the effectiveness of local delivery o f virgin coconut oil (VCO) in patients with periodontitis as an adjunct to subgingival instrumentation by comparing the clinical parameters of Probing Pocket Depth (PPD), Clinical Attachment level (CAL), Bleeding on Probing (BOP), Gingival Index (GI) and Plaque Index (PI) between groups with VCO and placebo applications. Methods: A total of 32 subjects were selected based on the inclusion criteria and were randomised into the test and control groups. At baseline, all clinical parameters were measured, followed by full mouth subgingival instrumentations after receiving oral hygiene education and instructions. Interventions of either VCO or placebo applications subgingivally were performed after 24 hours of subgingival instrumentations and were repeated for three more consecutive weeks. The measurement of the clinical parameters was repeated at 3, 6 and 9 months intervals with the use o f an acrylic stent with markings. Results: At baseline, the control and test groups showed no statistically significant differences in all mean parameters. At every review interval, intragroup comparison o f mean changes from baseline to every follow-up (at 3, 6 and 9 months) revealed statistically significant reductions in all parameters for both the test and control groups (p < 0.05). Meanwhile, the intergroup analysis revealed statistically significant differences in mean changes of PPD at 3 months (2.51±1.24 vs 1,82±1.43), 6 months (2.83±1.20 vs 2.01±l .41) and 9 months (2.72±1.15 vs 2.03±1.36), CAL at 3 months (1.89±1.48 vs 40.89±1.46), 6 months (2.09±1.47 vs 1.16±1.58) and 9 months (2.04±1.42 vs 1.10±l .61) and BOP at 3 months (2.51±1.24 vs 1.82±1.43), 6 months (2.83±1.20 vs 2.01±1.41) and 9 months (2.72±1.15 vs 2.03±1.36) between the test and control group (p<0.05), favouring more reductions in the test group compared to the control group. There were no significant differences in mean changes in GI and PI between the test and control groups at each review visit (p > 0.05).